The effectiveness of health education programs on human immunodeficiency virus/sexually transmitted infection awareness among adolescent girls in Bagalkot - Simmy Gavel; Pooja Todalabagi; Rachel Sushmita Daniel; Basavraj Mannapur (BLDE University Journal of Health Sciences, 2025)
BACKGROUND: Adolescence is a time of big changes – physically, emotionally, and socially. During this stage, many teenagers do not have enough accurate information about human immunodeficiency virus (HIV) and sexually transmitted infections (STIs), which make them more likely to get these infections. Education about health can help close this knowledge gap and teach teens how to protect themselves. OBJECTIVES: This study aimed to assess the knowledge, the teen girls have about HIV and STIs before the study and to evaluate how a health education program can improve their understanding and clear up false beliefs. METHODOLOGY: This study was conducted at B.V.V.S Polytechnic College in Bagalkot over 3 months (July–September 2024). It compared the students’ knowledge before and after the program without using a control group. A random sample of 90 girls aged 17–19 years was chosen. They answered a questionnaire about HIV and STIs before the education program. After the program, the same questionnaire was given again 3 months later. The results were analyzed to see how much their knowledge improved. RESULTS: The health education program made a big difference. The number of correct answers about how HIV is spread went up from 37.7% to 96.6%. Knowledge about ways to prevent HIV rose from 7.7% to 96.6%. Understanding of how HIV is detected increased from 67.7% to 93.3%. There was also a big drop in incorrect beliefs about how HIV is spread and prevented. CONCLUSION: Health education programs are very effective at teaching teenagers about HIV and STIs and clearing up misunderstandings. Adding these programs to school lessons are important to help young people make smart and safe health choices.